Open access in translation and interpreting studies: A bibliometric overview of its impact (1996-2015) - Rovira-Esteva, Sara; Olalla-Soler, Christian; Aixelá, Javier (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2021)
Open access (OA) is now a complex multifaceted phenomenon and one of the hottest topics under debate extending to other actors beyond academia. OA has been growing lately not only for ethical or ideological reasons, but also due to the pressure of formal mandates from public research funders. Many studies have shown that OA research outputs have greater citation impact as compared to similar toll-access (TA) ones, thus introducing a more pragmatic dimension for scholars considering OA. However, other studies claim there are many confounding factors that often have not been taken into account. To date, no study has been carried out concerning open access citation advantage (OAA) in TIS (translation and interpreting studies). This paper contributes to this debate by carrying out a bibliometric analysis by comparing the performance of documents in terms of accrued citations depending on access type in order to find out whether OA TIS research is cited more than its TA counterpart. We based our analysis on a sample of more than 20,000 TIS-related documents extracted from BITRA, covering a time span of 20 years (1996-2015). The main conclusion is that, although OA publications tend to be cited slightly more often than TA documents in our period of study, this difference is too small to either support or reject the OAA hypothesis in TIS.